Pinning in Radial Flow Moving Bed Reactor - Abd Aziz, Mohd Khairul Azhar (Universiti Teknologi PETRONAS, 2011)
For certain types of chemical reactors where the catalyst decays rapidly but reversibly, continuous operation is possible by use of a Radial Flow Moving Bed Reactor (RFMBR). A Continuous Catalyst Regeneration (CCR) reformer unit is one of the industrial units using the RFMBR. RFMBR can be simply described as a reactor where the catalyst flows downward by gravity and the feed gas flow radially across the reactor and leaves through a center pipe. In this type of reactor there is an upper limit on the gas flowrate imposed by a mechanical phenomenon called "pinning". "Pinning" is when the catalyst particles are pinned against the center pipe due to high gas velocity. Understanding the pinning and the fuctors influencing it is required for the CCR reformer process engineers before doing any plant optimization. By conducting the experiment we can study the effect the flowrate of gas to the maximum pinned film thickness.